Languages Speak Reconciliation: An Interdisciplinary Study on the Impact of National Language in Post War Reconciliation Sri Lanka - Jayathilaka, Aruna; Medagama, Thisiri; Panadare, Udeshini; Menike, Prawardhani (Technium Social Sciences Journal, 2022)
The Role of National Language is endorsed in different contexts and it has triggered an inspirited debate within the Sri Lankan political history when its discriminatory nature policies marked a triumph of linguist nationalism. The recognition of the Sinhala language as the only National Language in Sri Lanka and its dominance, drifted both communities apart causing frustration and tension among ethnic groups, which have ultimately culminated in ethnic strife that lasted almost three decades. National Languages, hence wield as a sociopolitical tool that demands a balance among languages, recognition, and policies. Similarly, Sri Lanka, in its path to reconciliation also demands a balance among National Languages, policies, and its recognition among the communities. This study thus explores the Role of National Language in promoting social cohesion and coexistence among ethnic groups to achieve anticipated “Reconciliation” within Sri Lankan social fabric. The paper draws upon a mixed approach employing qualitative methods, including in-depth interviews. Data were gathered from interviewing 20 undergraduates from the Faculty of Social Sciences and Languages at the Sabaragamuwa University of Sri Lanka. Data were coded and analyzed using thematic analysis. Findings revealed that the recognition of National languages in their due status will make a huge impact on fostering reconciliation within Sri Lankan Society. It is further not to be confused with the Link Language as a National Language since its duty in social integration is relatively limited in the cases where the understanding of cultural, traditional, and historical attributes of an ethnic community is more pronounced especially in grappling with attitudinal problems inherited within ethnic communities.